Kinetika Reaksi Demineralisasi Pada Isolasi Kitin Dari Limbah Cangkang Udang Industri Ebi - Ika Karina; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitin is natural polymer which used in biomedic sector mainly for injury healing, suture and dietery because chitin has antibacterial, antifungal and antiviral properties. Chitin content in natural material can be isolated using deproteinasi and demineralization process. This research objection is to determine demineralization reaction kinetics in chitin isolation with temperature and shrimp shell powder to HCl solution ratio. This research is started with 50 gr shrimp shell powder with 1 N HCl solution then heated with temperature such as 40°C and shrimp shell powder to HCl solution ratio such as 1:5, 1:10, 1:15 and 1:20 (gr/ml). Sample is taken with time interval 5, 10 and 15 minutes as much as 20 ml and washed until neutral pH. Next, sample is filtered using filter paper and then the solid part is analyzed in complexometry titration. Research result shows that reaction kinetics following pseudo second order and increasing of k value in a row of temperature increase is 0,00002 menit-1. Reaction rate constant in shrimp shell powder and HCl 1:5 (gr/ml) ratio is 0,000012 and increase to 0,00155 when ratio 1:20 (gr/ml) at 70oC.Key words : chitin, demineralization, kinetic reaction, polymer